Remarks at the Opening Session of the 2021 St. Petersburg Economic Forum - Malpass, David (World Bank, Washington, DC, 2021)
David Malpass, President of the World Bank, commented on 30 years of World Bank engagement with Russia. He discussed helping Russia contribute to global public goods, including its efforts toward a green transition that will benefit Russians and people around the world; and second, exchanging development knowledge. The Bank played an important role in support of institution building and reform, from the establishment of the federal treasury system to the digitization of customs and taxation. He commented on the economic context of St. Petersburg forum and then spoke about vaccines, debt, and climate.